Food proteins and peptides chemistry, functionality, interactions, and commercialization - Hettiarachchy, Navam S. (CRC Press, 2012)
"A unique blend of fundamentals and applied information, this book first provides readers with understanding of the chemistry and properties of food-derived proteins and peptides before looking at ways to maximize functional utilization in foods and dietary supplements. A valuable resource for nutritionists, nutraceutical experts, and pharmacologists involved with product development and dietary supplement applications, the book describes physicochemical properties and interactions involved in regulating biological function. It also covers practical considerations regarding properties such as solubility, emulsification, foaming, and gelling, as well as protein modifications, both chemical and enzymatic, to improve functionalities"--